Computer Vision Syndrome among Call Center Employees at Telecommunication Company in Bandung - Ghea Nursyifa; Putri Teesa Radhiyanti Santoso; Ine Renata Musa (Althea Medical Journal, 2016)
Background: The occurrence of Computer Vision Syndrome (CVS) at the workplace has increased within decades due to theprolonged use of computers. Knowledge of CVS is necessary in order to develop an awareness of how to prevent and alleviate itsprevalence . The objective of this study was to assess the knowledge of CVS among call center employees and to explore the most frequent CVS symptom experienced by the workers.Methods: A descriptive cross sectional study was conducted during the period of September to November 2014 at Telecommunication Company in Bandung using a questionnaire consisting of 30 questions. Out of the 30 questions/statements, 15 statements were about knowledge of CVS and other 15 questions were about the occurrence of CVS and its symptoms. In this study 125 call center employees participated as respondents using consecutive sampling. The level of knowledge was divided into 3 categories: good (76–100%), fair (75–56%) and poor (<56%). The collected data was presented in frequency tabulation.Results: There was 74.4% of the respondents had poor knowledge of CVS. The most symptom experienced by the respondents was asthenopia.Conclusions: The CVS occurs in call center employees with various symptoms and signs. This situation is not supported by good knowledge of the syndrome which can hamper prevention programs. [AMJ.2016;3(2):181–21]DOI: 10.15850/amj.v3n2.789